'I am answerable for the Cornish': The genesis of the Revd Robert Williams's Lexicon-Cornu Britannicum and the significance of the Peniarth Library's Hengwrt Manuscripts in his later research. (1st May 2011) - Williams, Derek R.
At the very bottom of the Welsh-language memorial stone in Culmington churchyard, Shropshire, to the Revd Robert Williams, Celtic scholar and antiquary, are two lines of Cornish: Yw dywydhys: / My a wor yn ta lemyn (It is finished: / I know it well now). The first line was spoken by Christ on the cross, while the second consists of words from the final speech of Moses in Origo Mundi, the first play in the late fourteenth-century Cornish-language cycle of mystery plays known as the Ordinalia. Williams's important place in the discovery and examination of Cornish texts in the middle of the nineteenth century is well known or, at least, acknowledged by scholars from Jenner through to Murdoch. His memorial describes him as 'the learned author of the Lexicon Cornu-Britannicum and of several other books', while his part in the discovery at Peniarth Library of the only extant copy of a previously unknown Cornish drama, the 'Ordinale de vita sancti' or Beunans Meriasek (the Life of St Meriasek), was a pivotal moment in Cornish-language studies. Less well explored, perhaps, is the reason that Welshman Robert Williams chose to concentrate on Cornish in the first place and how important his Cornish-language studies were to him. This article looks at the likely impact of his first appointment as curate of Llangernyw in west Denbighshire. It then examines the few references to his research and writing in the diary that he kept between 1832 and 1847; his correspondence with other nineteenth-century Celtic scholars, such as Whitley Stokes and D. Silvan Evans; and the important place occupied by William Wynne's 'precious library' at Peniarth, Merioneth in the work of these scholars.